(untitled) (Revista Educação, Artes e Inclusão, 2022)
PECS is an alternative communication method used by autistc people who did not develope the language or who have speech deficits. The objective of this article is to perform a bibliographic research through the come after data bases: SciELO, PePSIC and the thesis and dissertations database CAPES, in order to answer the following question: What benefits has the PECS brought to people with autism? The date delimitation was between the years 2000 and 2016, only brazilian scientific studies which describe the intervention of the PECS and their respective results in autistic people were analyzed. Twenty-three scientific studies were found through the keywords: "PECS", "Alternative Communication", "Autism and PECS" in any field, however only eight met the criteria of the research. The results showed that PECS promotes communication and reduces typical autismo behaviors, but the low number of studies in three data bases over the sixteen-year period shows that the use of PECS in autistic individuals is a scarce subject requiring empirical studies that demonstrate the effects and experiences of this method.